Oneyda Alvarenga e a obra música popular brasileira (1945) - Machado, Vanessa Bertoncello (2025)
The purpose of this dissertation, whose research object is to analyze book Música Popular Brasileira (1982), is to find out how the young aspiring poet and pianist, Oneyda Alvarenga, built her career, first as a student of the writer Mário de Andrade and then as director of the Discoteca Pública Municipal de São Paulo (Municipal Public Discotheque of São Paulo). In addition, this work verified the intellectual and researcher's progress in the development of valuable projects for national culture, ranging from the preparation and cataloging of folkloric material in the institution, to the development of actions aimed at the general public, based on the folkloric research undertaken. The record concerts, the establishment of an organizational model for the Discotheque, to the writing of more voluminous research and works, such as the book and object of study of this research, Música Popular Brasileira, written in 1945. A work of great weight, it stands out for the rich folkloric content that accompanies it, rescuing expressive details of Brazilian culture from that period. The Missão de Pesquisas Folclóricas is one of the determining points both for the writing of the book and for the other activities that the author would develop within the Discoteca. Oneyda Alvarenga therefore became a leading figure, as she contributed to the insertion of modernist ideals into the systematization of national culture.